Maxwell McCombs, 35 years of a limitless theory: a profile - José Afonso Jr.; Ana Paula da Rosa; Pedro Paulo Procópio (Brazilian Journalism Research, 2008)
This paper intends to draw a profile of 35 years of agenda-setting theory continuous development, as well as to present a parallel with its creator, Professor Maxwell McCombs. The approach adopted is to contextualize the agenda-setting theory with some trends that had influence on its appearance and development during the last three decades. This profile also documents some statements of Professor McCombs´ participation in his first visit to Brazil, including his opening session speech at the 5th Congress of the Brazilian Society of Journalism Researchers – SBPJOR – and the lecture he gave in the Postgraduate Program of Communication Studies at the Federal University of Pernambuco, Brazil. Both events occurred in November 2007. Until now, this is the first and only visit by Professor McCombs to Brazil.